2017
DOI: 10.1080/10790268.2017.1370522
|View full text |Cite
|
Sign up to set email alerts
|

Linking spinal cord injury rehabilitation between the World Wars: The R. Tait McKenzie legacy

Abstract: Spinal cord injury (SCI) medicine emerged after World War II due to mass casualties, which required specialized treatment centers. This approach to categorical care, however, was first developed during World War I, led by pioneers R. Tait McKenzie and George Deaver, who demonstrated that soldiers disabled by paralysis could return to society through fitness/mobility, recreational and vocational training. McKenzie, a Canadian and the first professor of physical therapy in the US, influenced Deaver and military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…68 A crucial early development was the formation of specialized neurorehabilitation treatment centers, pioneered by Robert Tait McKenzie (1867McKenzie ( -1938, George Deaver (1890-1973), and Harry Botterell (1906Botterell ( -1997, among other physicians. 15 They demonstrated that intensive physical and occupa-tional therapy regimens could improve outcomes and even help paralyzed soldiers return to civilian society.…”
Section: World War Imentioning
confidence: 99%
See 1 more Smart Citation
“…68 A crucial early development was the formation of specialized neurorehabilitation treatment centers, pioneered by Robert Tait McKenzie (1867McKenzie ( -1938, George Deaver (1890-1973), and Harry Botterell (1906Botterell ( -1997, among other physicians. 15 They demonstrated that intensive physical and occupa-tional therapy regimens could improve outcomes and even help paralyzed soldiers return to civilian society.…”
Section: World War Imentioning
confidence: 99%
“…A professional athlete and gymnast, McKenzie developed an interest in physical education and was appointed the first professor of physical therapy in the US upon joining the faculty at the University of Pennsylvania in 1904 and emphasized scientific rigor to develop exercise regimens for both healthy and disease states. 15 In 1915, he joined the British Royal Army Medical Corps in WWI, where he introduced physical therapy regimens, occupational therapy, and vocational retraining for injured soldiers. 16 His manual Handbook of Physical Therapy was referenced by American, British, and Canadian armed forces to establish physical rehabilitation efforts.…”
Section: World War Imentioning
confidence: 99%
“…The first big improvement in SCI patient care came as consequence of the drastically high numbers of deaths caused by SCI during World War I, due to low level of palliative cares provided to patients. As a consequence, a significant effort was made to establish multidisciplinary care centers and recruiting specialist to treat and follow civilians and military in the World War II [ 3 , 4 ]. As a result, an improvement in life expectancy of patients with SCI in the last decades was achieved, disclosing levels slightly lower than the average rate for non-SCI individuals.…”
Section: Overview Of Spinal Cord Injurymentioning
confidence: 99%
“…Granger's legacy at BCH in physical therapeutics likely contributed to the development of the first U.S. spinal cord injury inpatient unit in the early 1930s, an effort led by neurosurgeon Donald Munro . The care provided there included physical restoration and prevention of bladder and skin complications . Although recognition of Granger's contribution is important to the history of PM&R at HMS, there is little evidence that this had any impact on PM&R at MGH.…”
Section: Pmandr History Mgh/hms: the Granger Eramentioning
confidence: 99%